Democratic Neoliberalism and new debt crisis in Argentina - Castorina, Emilia (2022)
The main goal of this paper is to analyse the way in which external debt conditions democratization processes in Argentina at two levels: first, by understanding democratic neoliberalism as a new form of power and social disciplining; and second, by briefly describing debt crises (and its many creative financial hits) as a way to understand the political power of finance capital.